2014
DOI: 10.1002/ebch.1979
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane in context: Combined and alternating paracetamol and ibuprofen therapy for febrile children

Abstract: There is some evidence that both alternating and combined antipyretic therapies may be more effective at reducing temperatures than monotherapy alone. However, the evidence for improvements in measures of child discomfort remains inconclusive. There is insufficient evidence to decide which of combined or alternating therapy might be more beneficial. Future research needs to measure child discomfort using standardized tools, and assess the safety of combined and alternating antipyretic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Because acetaminophen and ibuprofen act as COX-enzyme inhibitors on a central respectively a peripheral level they maximally inhibit PGE2 synthesis produced by exercise-induced IL-6 release. Whilst COX has been shown to not affect forearm sweating 28 , a clinical study suggested that the combined therapy of acetaminophen and ibuprofen is more effective in lowering TC during fever 29 . The present study expands this observation to an exercise setting.…”
Section: Discussionmentioning
confidence: 99%
“…Because acetaminophen and ibuprofen act as COX-enzyme inhibitors on a central respectively a peripheral level they maximally inhibit PGE2 synthesis produced by exercise-induced IL-6 release. Whilst COX has been shown to not affect forearm sweating 28 , a clinical study suggested that the combined therapy of acetaminophen and ibuprofen is more effective in lowering TC during fever 29 . The present study expands this observation to an exercise setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although associations can obviously show additive or even synergistic effects, currently the combination of paracetamol and ibuprofen, whether given alternately or together, is not recommended for the treatment of fever [18]. There is insufficient evidence to state that combined/alternating treatment in febrile states can be of more benefit, considering that the clinical efficacy of 15 mg/kg paracetamol monotherapy currently enables excellent management of the symptom.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding use of medications to treat fever, antipyretics such as paracetamol and Ibuprofen were used. Health professionals frequently recommend treatment regimens for children with fever that either combine or alternate paracetamol and ibuprofen [23,24]. However, the consequences of under-and over-treatment with antipyretics including mucosal lesions, gastrointestinal discomfort such as dyspepsia, and severe gastrointestinal complications such as perforated ulcer, gastrointestinal bleeding has been reported [25].…”
Section: Resultsmentioning
confidence: 99%